Bioethics in a liberal society - Charlesworth, M. J. 1925-2014 (Cambridge University Press, 1993)
We live in a liberal, democratic, multicultural society where ideally the values of personal liberty and autonomy are paramount. In such a society the state, through the law, should not be concerned with telling people how they should live their lives. In spite of this, many of the ethical stances taken in liberal societies are paternalistic and authoritarian. This readable and balanced book is an original discussion of contemporary issues in bioethics. Max Charlesworth argues that as there can be no public consensus on a set of core values – liberal societies accept a variety of religious, non-religious, political and moral stances - there should be a plurality of ethical stances as well. On this basis he discusses issues such as the ending of human life, the new reproductive technologies and ethical distribution of limited health-care resources, particularly hospital care